Short‐term natural course of esophageal thermal injury after ablation for atrial fibrillation. (7th June 2022) - Ishidoya, Yuki; Kwan, Eugene; Dosdall, Derek J.; Macleod, Rob S.; Navaravong, Leenhapong; Steinberg, Benjamin A.; Bunch, T. Jared; Ranjan, Ravi
Abstract: Introduction: Esophageal injury is rare but potentially a devastating complication of atrial fibrillation (AF) ablation. The goal here was to provide insight into the short‐term natural history of esophageal thermal injury (ETI) after radiofrequency catheter ablation (RFCA) for AFby esophagogastroduodenoscopy (EGD). Methods: We screened patients who underwent RFCA for AF and EGD based on esophageal late gadolinium enhancement (LGE) in postablation magnetic resonance imaging. Patients with ETI diagnosed with EGD were included. We defined severity of ETI according to Kansas City classification: type 1: erythema; type 2: ulcers (2a: superficial; 2b deep); type 3 perforation (3a: perforation; 3b: perforation with atrioesophageal fistula [AEF]). Repeated EGD was performed within 1−14 days after the last EGD if recommended and possible until any certain healing signs (visible reduction in size without deepening of ETI or complete resolution) were observed. Results: ETI was observed in 62 of 378 patients who underwent EGD after RFCA. Out of these 62 patients with ETI, 21% (13) were type 1, 50% (31) were type 2a and 29% (18) were type 2b at the initial EGD. All esophageal lesions, but one type 2b lesion that developed into an AEF, showed signs of healing in repeated EGD studies within 14 days after the procedure. The one type 2b lesion developing into an AEF showed an increase in size and ulcer deepening in repeat EGD 8 days after the procedure. Conclusion: We found that all ETI which did not progress to AEF presented healing signs within 14 days after the procedure and that worsening ETI might be an early signal for developing esophageal perforation.